2022
DOI: 10.1177/20503121221095324
|View full text |Cite
|
Sign up to set email alerts
|

The effects of vitamin E on non-proliferative diabetic retinopathy in type 2 diabetes mellitus: Are they sustainable with 12 months of therapy

Abstract: Introduction: Prolonged uncontrolled hyperglycaemia has shown to cause oxidative stress, inflammation, thrombosis and upregulation of angiogenesis in diabetics, which all contributes to diabetic retinopathy development and progression. Vitamin E is found to have anti-inflammatory, anti-oxidative, anti-thrombogenic and anti-angiogenesis which could play an important role in early treatment of diabetic retinopathy. This study aims to investigate the effect of Tocotrienol-rich vitamin E (Tocovid) on the progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 34 publications
(46 reference statements)
0
13
0
Order By: Relevance
“…The area of DME, on the other hand, was significantly decreased, by 48.38% in the vitamin group, while there was no significant change in the placebo group. For serum VEGF level at 12 months, there was no significant difference between the two groups, or when compared with baseline in each group [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The area of DME, on the other hand, was significantly decreased, by 48.38% in the vitamin group, while there was no significant change in the placebo group. For serum VEGF level at 12 months, there was no significant difference between the two groups, or when compared with baseline in each group [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…Assessment of retinal hemorrhage, one of many retinal lesions in DR, alone might not be a good surrogate for assessment of DR progression. In addition, assessment of DME from retinal photographs may not be as reliable as from optical coherence tomography (OCT) [ 67 ]. In the pilot study, the authors aimed to study vitamin B, which was found to lower the risk of cardiovascular diseases and nephropathy, in the treatment of DR.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, optimal oxidative balance protects against micro-and macrovascular complications of diabetes through shared endpoints of endothelial dysfunction, low-grade in ammation and accelerated atherosclerosis [4,21]. Diabetic nephropathy, cardiovascular disease, stroke and related complications that are more prevalent in those with poorer antioxidant status could contribute to higher mortality [36,37].Finally, beyond diabetes, higher overall antioxidant exposure has been associated with lower risks of cancer, lung disease, [41,44]. However, direct evidence on the effects of lifestyle changes and antioxidant supplements on hard clinical outcomes like diabetic retinopathy remains limited [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Ho, et al [68] showed that TRF (200 mg twice daily for 12 months) was effective in preventing early diabetic retinopathy compared to placebo. Diabetic retinopathy is a very common microvascular complication of T2D and makes a major contribution to blindness and vision loss in adults [68].…”
Section: The Tocotrienol-rich Fraction (Trf) From Palm Oil May Be Ben...mentioning
confidence: 99%